12α-Hydroxy-3,27-dioxooleanano-28,13-lactone - Hu, Jun-yi (International Union of Crystallography, 2012)
There are two independent molecules in the asymmetric unit of the title compound, C(30)H(44)O(5). They comprise a triterpenoid skeleton of five six-membered rings and a five-membered lactone ring. The five six-membered rings are all trans-fused. In both independent molecules the D rings adopt a slightly distorted half-chair conformation due the presence of the lactone ring while the other four six-membered rings all adopt chair conformations. The characteristic carbon–carbon double bond of the oleanoic skeleton is absent. Intermolecular O—H⋯O hydrogen bonds between the hydroxy and carbonyl groups occur in the crystal structure.